A Finite-Time Fractional-Order Error Extended State Observer for Hypersonic Vehicle - Mingfei Zhao; Jia Song; Yunlong Hu; Wenling Li (International Journal of Aerospace Engineering)
To address the challenges posed by strong coupling, nonlinearity, and rapid time-varying dynamics in hypersonic vehicle (HV), this study presents an active disturbance rejection control (ADRC) scheme based on finite-time fractional-order error extended state observer (FTFOEESO). To begin, a control-oriented HV model is established. Subsequently, the FTFOEESO is developed to accurately estimate and compensate for strong disturbances and uncertainties. Unlike traditional FOESO, this observer does not alter the physical interpretation of the estimated variables or introduce unknown disturbances. Furthermore, this approach has demonstrated significant potential in mitigating high-frequency noise. Theoretical analysis has confirmed that the observation error of FTFOEESO is uniformly bounded. Finally, this paper conducts experiments using both conventional simulation and semiphysical simulation systems. Simulation studies and comparisons have revealed that the ADRC based on FTFOEESO possesses superior anti-interference and antinoise capabilities.